(untitled) (Journal of Medicine, 2019)
Background: Tumour registry data on intracranial and intraspinal tumours from a newly set up tertiary hospital of Bangladesh is presented here to provide substantial information about the current trends. Materials & methods: Hospital records of patients admitted under the neurosurgery service between January 2016 upto December 2017 were evaluated. Causes with a principal diagnosis of brain and spinal cord tumours were identified. Diagnosis with WHO grading and the histological subtypes are recorded. Results: 86 cases of various tumours were retrieved out of total 98 neurosurgical cases. 70 of these tumours were of intracranial origin and 16 of intraspinal origin. Male to female ratio was approximately 1.28:1. The mean age of the patients was 45.9 years (range 3-75 years). Paediatric and adult patients accounted for 12.6% and 87.4% respectively. Most of the tumours were found in the 6th decade. Paediatric intracranial tumours were predominately by medulloblastoma while adult population showed highest incidence of astrocytic tumours. Some rare entities were also encountered such as intracranial germinoma, Diffuse large B cell lymphoma (DLBCL) and squamous cell carcinoma in a pre-existing intracranial epidermoid cyst. Conclusions: Distribution of CNS tumour among this population gives a glimpse of the prevalence rate of such tumours in our community. This data can be linked to other national and international tumour registry for improved therapeutics and research. J MEDICINE JUL 2019; 20 (1) : 34-37